1998
DOI: 10.1116/1.590390
|View full text |Cite
|
Sign up to set email alerts
|

Resist processes for hybrid (electron-beam/deep ultraviolet) lithography

Abstract: Articles you may be interested inDeep ultraviolet photolithography capability of ZEP520A electron beam resist for mix and match lithography This article describes the different mix and match writing strategies using both an optical deep ultraviolet ͑DUV͒ stepper ͑ASML/90͒ and an electron-beam ͑e-beam͒ system ͑LEICA VB6HR͒ with both positive and negative tone chemically amplified resists. These resists, mainly developed for DUV applications, have shown very good performance under e-beam exposure. Negative tone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…This induces delays that could harm the resist performance. In [6], it was found that delays, as long as they remain short (<2 h) are not an issue, and larger delays in vacuum do not affect the resist performance. In our process, we transport the wafers in a dry environment, which reduces the wafer-to-wafer and lot-to-lot variability and renders stable CD response for delays up to 24 h. Even though the dry environment aids in the resist stabilization, the wafers are scheduled to be processed immediately to ensure minimal unnecessary delays.…”
Section: Delay Managementmentioning
confidence: 96%
See 1 more Smart Citation
“…This induces delays that could harm the resist performance. In [6], it was found that delays, as long as they remain short (<2 h) are not an issue, and larger delays in vacuum do not affect the resist performance. In our process, we transport the wafers in a dry environment, which reduces the wafer-to-wafer and lot-to-lot variability and renders stable CD response for delays up to 24 h. Even though the dry environment aids in the resist stabilization, the wafers are scheduled to be processed immediately to ensure minimal unnecessary delays.…”
Section: Delay Managementmentioning
confidence: 96%
“…There have been a number of studies on the use of resists in hybrid mode [6][7][8]. In contrast to these works, we targeted the whole patterning process, including the dry etching that follows the hybrid lithography.…”
Section: Resist Process Windowmentioning
confidence: 99%
“…In fact, light falling on the substrate through a thin resist film undergoes an infinite series of reflections at the boundaries between the thin film and the air as well as at the film/ substrate interface. The incoming and outgoing waves interfere in the film, causing constructive and destructive interferences which lead to creating standing waves [14][15][16][17]. Physicists call this film stack a Fabry-Perot etalon.…”
Section: Duv Exposurementioning
confidence: 99%
“…In contrast, electron beam lithography is capable of very high resolution, but at a much reduced exposure rate compared to optical lithography. Hybrid lithography combines the best characteristics of these two lithography techniques by mixing the use of optical lithography for the large area, low resolution parts of the pattern with the use of e-beam lithography for the small area, high resolution parts of the pattern [2]. Usually this mixed lithography approach needs to be done in separate lithographic patterning steps using a different resist layer for each lithographic technique.…”
Section: Introductionmentioning
confidence: 99%